Dissecting the Flash Chemistry of Electrogenerated Reactive Intermediates by Microdroplet Fusion Mass Spectrometry - Hu, Jun; Wang, Ting; Zhang, Wen‐Jun; Hao, Han; Yu, Qiao; Gao, Hang; Zhang, Nan; Chen, Yun; Xia, Xing‐Hua; Chen, Hong‐Yuan; Xu, Jing‐Juan (Angewandte Chemie International Edition, 2021)
A novel mass spectrometric method for probing the flash chemistry of electrogenerated reactive intermediates was developed based on rapid collision mixing of electrosprayed microdroplets by using a theta‐glass capillary. The two individual microchannels of the theta‐glass capillary are asymmetrically or symmetrically fabricated with a carbon bipolar electrode to produce intermediates in situ. Microdroplets containing the newly formed intermediates collide with those of the invoked reactants at sub‐10 microsecond level, making it a powerful tool for exploring their ultrafast initial transformations. As a proof‐of‐concept, we present the identification of the key radical cation intermediate in the oxidative dimerization of 8‐methyl‐1,2,3,4‐tetrahydroquinoline and also the first disclosure of previously hidden nitrenium ion involved reaction pathway in the C−H/N−H cross‐coupling between N,N′‐dimethylaniline and phenothiazine. Microreactor on the fly: A special microreactor that permits mass spectrometric probing the flash chemistry of electrogenerated reactive intermediates was demonstrated based on collision mixing of electrosprayed microdroplets, which employed a theta‐glass capillary integrated with carbon bipolar electrodes to produce short‐lived intermediates in situ.